Enhanced Modulation of Streamflow Flash Droughts by Reservoir Operations in India - Rajesh Singh; Vimal Mishra (Water Resources Research)
Abstract Streamflow flash droughts (SFDs) occur due to a rapid decline in streamflow and cause major challenges associated with water availability for downstream ecosystems, hydropower generation, and irrigation water demand. Human interventions such as reservoir operations and reservoir storage can considerably influence streamflow variability. However, the crucial role of dams/reservoirs on the occurrence of SFDs in India remains unexamined. Using a combination of hydrological and hydrodynamical models, we examined the role of reservoirs on SFDs in India during 1971–2020. Reservoirs play a considerable role in the occurrence of SFDs during the summer monsoon season (June‐September) in India. The frequency and severity of SFDs in the presence of reservoirs are substantially lesser than in the absence of them. In addition, high and low antecedent reservoir storage conditions before meteorological flash droughts (MFDs) do not support the rapid decline of streamflow (i.e., SFDs) downstream of reservoirs, while the medium reservoir storage conditions prior to MFDs favor the development of SFDs. Similar to conventional (or long‐term) streamflow droughts (SDs), SFDs are more frequent in the El Nino phase than in the La Nina phase. Unlike the long‐term streamflow droughts, the implementation of dams considerably reduces the frequency of SFDs during both the negative and positive phases of El Nino Southern Oscillation. Overall, our findings demonstrate the considerable role of human interventions in flash drought occurrence, as SFDs are triggered by MFDs but modulated by reservoir storage and operations.